Development of inhaled formulation of modified clofazimine as an alternative to treatment of tuberculosis: Clofazimine inhaled formulation for tuberculosis - Healy, Anne-Marie (My University, 2020)
Inhalation drug delivery provides a possible useful alternative to oral drug delivery in the treatment of tuberculosis (TB). This work evaluated inclusion complexes of clofazimine (CFZ), an anti-TB drug with low aqueous solubility and potential gastric degradation, in β-cyclodextrin (βCD), γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and sulfobutyl-ether-β-cyclodextrin. A phase solubility study indicated that βCD showed the best inclusion capacity for CFZ, so a CFZ:βCD complex (1:7) was selected for further studies. Particle engineering was performed using spray drying to obtain powders with suitable characteristics for pulmonary delivery and l-leucine was added to enhance powder dispersibility. Thermal and spectroscopic analyses indicated the CFZ:βCD integrity after spray drying, and the presence of l-leucine resulted in less hygroscopic and rougher particles, and a less agglomerated powder. All formulations, and especially those containing l-leucine, showed suitable in vitro deposition performance in the Next Generation Impactor and presented higher aqueous solubility compared to the free drug. In vitro studies showed low toxicity against Calu-3 and CFZ retention in the cell monolayer and apical compartment. These results suggest that the inhalation formulation composed of CFZ:βCD plus l-leucine should improve CFZ pulmonary bioavailability and provide an alternative treatment for TB, acting on the main infection site of the disease.
PUBLISHED
Keywords: Pulmonary delivery; Tuberculosis; Clofazimine; Cyclodextrin; L-leucine